STRENGTHENING HEALTH RESEARCH FOR CLIMATE CHANGE IN AFRICA - Yitambe, Andre; Warutere, Peterson Njogu; Kibarraa, Kenneth Rucha (International Journal of Research -GRANTHAALAYAH, 2018)
Despite the complexity of climate change and health research, studies conducted are still remaining non-interdisciplinary and non -multidisciplinary. A number of literatures has demonstrated the complexity for carrying research on climate change from social sciences, climate sciences to public health sciences. Social scientists look at the climate change as a social constructedness when climate scientists look at the climate change in term of terrestrial, oceanographic, and atmospheric change due to carbon dioxide emission, greenhouse emission, and ozone depletion. Health research studies have demonstrated the impact of climate change on health In Africa, Middle Income Countries as well as in Advanced Industrialized countries. Drawn on ethno-monographic studies, desk-based studies, secondary data and review of literatures relative to climate change and health, this paper examines the impact of climate change in Africa. The findings reveal three impacts of climate change: direct effects, indirect effects and postulated effects. The findings inform Disaster Risk Reduction Policy Makers on mitigation measure and adaption.